Effects of mirror therapy vs modified constraint induced movement therapy on upper extremity in subacute stroke patients - kaviraja, Kamatchi; Tharani, G; Yuvarani, G; Kaviraja, N; S, Jenifer Augustina; Aarthi, C (Bangladesh Journal of Medical Science, 2021)
Objective: To compare and to examine the effectiveness of mirror therapy and modified constraint induced movement therapy (mCIMT) on upper extremity in subacute stroke patients. Background: Stroke or cerebral vascular accident is sudden dead of the brain cells due to inadequate blood flow. The WHO defines stroke as rapidly developing clinical signs of focal disturbance of cerebral function, with symptoms lasting for 24hrs or longer or leading to death, with no apparent cause other than of vascular origin. The most common consequence of stroke is loss of upper limb function. The protocol planned for improving the function of upper limb are mirror therapy and modified constraint induced movement therapy (mCIMT). Mirror therapy is a simple and inexpensive treatment which uses the visual information activating the premotor and motor cortex of the brain. This is explained by activation of so called mirrorneuron system. Whereas mCIMT utilises the redundant pathway in brain through neuro plasticity. Methodology: A total of 30 participants with subacute stroke were selected. The inclusion criteria are both gender of age 55-70 years and duration of 2-12 months of post stroke. Participants with mini mental state examination score<24, uncontrolled systemic hypertension, severe shoulder subluxation, previous stroke and severe cardiac failure were excluded. The outcome measures were measured using Upper Extremity Functional Index (UEFI) and Fugl Meyer Upper Extremity Scale. Procedure: All 30 participants with sub-acute stroke were divided into two groups. Both the group individuals were assessed for pre test using Fugl Meyer Upper Extremity Scale and Upper Extremity Functional Index Scale. Group A (15) was assigned to mirror therapy for 5 days a week, for 4 weeks and rest intervals was given. Similarly group B (15) was assigned to modified constraint induced movement therapy for 5 days a week, for 4 weeks. Both the groups were given conventional therapy for 20 mins. At the end of study subjects were assessed for post test using UEFI and Fugl Meyer upper extremity scale. Results: The Modified Constraint Induced Movement (mCIMT) is more effective than Mirror Therapy in improving the hemiparetic upper extremity in subacute stroke patients. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.323-329